2020
DOI: 10.1186/s12872-020-01718-4
|View full text |Cite
|
Sign up to set email alerts
|

Meigs’ syndrome mimicking heart failure with preserved ejection fraction: a case report

Abstract: Background Meigs’ syndrome is a rare disease characterized by a triad of presentations, including benign ovarian tumor, ascites, and pleural effusion. However, a clinical diagnosis of Meigs’ syndrome remains challenging because pleural and ascitic effusions can be common findings in a variety of underlying conditions. Furthermore, these findings can often be misdiagnosed as pleural and peritoneal dissemination caused by potentially malignant tumors, leading to the administration of improper treatment. Case p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Supporting this possibility, the patient’s postoperative transthoracic echocardiography demonstrated that the degree of aortic and mitral regurgitation had become trivial at 1-month post-surgery. However, surgical resection is preferred in Meigs syndrome with similar symptoms such as respiratory failure and pleural effusion because diuretics are ineffective [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this possibility, the patient’s postoperative transthoracic echocardiography demonstrated that the degree of aortic and mitral regurgitation had become trivial at 1-month post-surgery. However, surgical resection is preferred in Meigs syndrome with similar symptoms such as respiratory failure and pleural effusion because diuretics are ineffective [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its presentation with a triad of ascites, pleural effusion, and ovarian tumor, which is more often seen in more serious conditions, makes it challenging to diagnose Meigs syndrome, a benign disease [ 6 ]. Malignant conditions presenting as adnexal masses in pediatric and adolescent patients include germ cell tumors, sex cord-stromal tumors, epithelial ovarian tumors, and metastatic tumors [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because several conditions are linked to the development of these common indications, the correct diagnosis and treatment are frequently missed. 7 The cause of Meigs’s condition is still unknown. Ascites are a common symptom of ovarian tumors, and numerous causes have been proposed, including tumor torsion and restriction of venous drainage.…”
Section: Discussionmentioning
confidence: 99%